If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(u+8)=6u+24
We move all terms to the left:
2(u+8)-(6u+24)=0
We multiply parentheses
2u-(6u+24)+16=0
We get rid of parentheses
2u-6u-24+16=0
We add all the numbers together, and all the variables
-4u-8=0
We move all terms containing u to the left, all other terms to the right
-4u=8
u=8/-4
u=-2
| 9(2)-9x=10 | | -6u+28=-8(u-5) | | 5(5h-2)=-35 | | 1x+13=2x-8 | | 9.9t=-9.9 | | 3*10+y=80 | | 27.5x=23.25+17x | | 25+5x=130 | | 6/8=2(x+4)/3x+20 | | 2(w+8)=-2w-16 | | 4(3x-2)-x=3x-4x | | 5^x=x-2 | | 190-x=216 | | 23.25+17h=27.50h | | 4x-8+x+8+x=180 | | -4u+4=-8(u+4) | | 27.5r=23.25+17 | | 3x-5(x-3)=-+3x+7 | | 27-y=99 | | 6+9x=4+23x | | 624=0.04x^2−5x+700 | | 6y=(2y+32) | | 60-4x=90-24x | | 4^(6x)=3000 | | 1/2(10-8x)+6x=19 | | x-7=2x-55 | | 5^2x=150000 | | 27b=35 | | 1/3•d=6 | | 2x+1=-3x+16 | | u+2/5=-1/6 | | 5(v-2)-2v=20 |